TransLatin: The Transnational Impact of Latin Theatre from the Early Modern Netherlands : Qualitative and Computational Analyses - Bloemendal, Jan; Wouters, Dinah (Drama and Theatre in Early Modern Europe, 2026)
What do a Dutch school drama and a Swedish royal tragedy have in common? TransLatin uncovers the unexpected journeys of Latin plays from the Low Countries across early modern Europe. Bridging qualitative and computational methods, the volume reveals previously uncharted networks of circulation, translation, and reuse. New data and visualisations offer insights into the infrastructure of transmission: print networks, pedagogical institutions, and multilingual intermediaries. Case studies range from biblical drama and Jesuit theatre to the Everyman tradition and the Swedish Rosimunda . By combining traditional scholarship with Digital Humanities, TransLatin redefines the boundaries of early modern theatre studies and offers a model for transnational literary research. Contributors are Dinah Wouters, Andrea Peverelli, Jan Bloemendal, and James A. Parente, Jr..